Kontestasi kebhinekaan pancasila dalam ekosistem media sosial - Ade Putranto Prasetyo Wijiharto Tunggali; Ahmad Nasher (Jurnal Komunikasi Universitas Garut: Hasil Pemikiran dan Penelitian, 2026)
Abstract The digital age has brought significant changes to society’s communication patterns, including the mechanisms for disseminating national values. Current trends indicate a shift in perception, whereby values such as courtesy, mutual respect, and tolerance—which serve as the nation’s foundational bonds—are increasingly viewed as irrelevant by some citizens. There is a growing tendency to regard local culture as a traditional entity incompatible with modern progress. Consequently, a paradigm shift is needed in national life to respond to intensive interaction with foreign cultures. This study analyzes digital communication patterns to promote the values of Pancasila’s diversity through social media platforms. Pancasila, as the state ideology, now faces both challenges and new opportunities amid the dominance of social media as the primary communication platform. This research aims to examine these changes and analyze effective digital communication patterns to promote the values of Pancasila’s diversity. This study aims to examine these changes and analyze effective digital communication strategies for promoting the values of Pancasila’s diversity. Using a qualitative approach, this study explores various strategic methods to enhance public awareness and participation. The research findings indicate that strategies based on interactive content, collaboration with public figures (influencers), and the optimization of social media algorithms can significantly enhance the effectiveness of disseminating the values of Pancasila. This study concludes that it is crucial to adapt communication strategies to advancements in digital technology and the characteristics of contemporary audiences. This is essential to ensure that national values remain relevant, resilient, and well-received by the younger generation amidst the dynamic currents of globalization. Keywords: Pancasila values; social media; communication patterns.   Abstrak Era digital telah membawa perubahan signifikan dalam pola komunikasi masyarakat, termasuk dalam mekanisme penyebaran nilai-nilai nasional. Fenomena saat ini menunjukkan adanya pergeseran persepsi di mana nilai-nilai kesopanan, saling menghormati, dan toleransi sebagai perekat dasar bangsa mulai dianggap kurang relevan oleh sebagian warga negara. Muncul kecenderungan untuk memandang budaya lokal sebagai entitas tradisional yang tidak kompatibel dengan kemajuan zaman. Akibatnya, diperlukan perubahan paradigma dalam kehidupan berbangsa dan bernegara guna merespons interaksi intensif dengan budaya asing. Studi ini menganalisis pola komunikasi digital untuk mempromosikan nilai-nilai Kebhinekaan Pancasila melalui platform media sosial. Pancasila, sebagai ideologi negara, kini menghadapi tantangan sekaligus peluang baru di tengah dominasi media sosial sebagai platform komunikasi utama. Penelitian ini bertujuan mengkaji perubahan tersebut serta menganalisis pola komunikasi digital yang efektif untuk mempromosikan nilai-nilai Kebhinekaan Pancasila. Menggunakan pendekatan kualitatif, studi ini mengeksplorasi berbagai metode strategis untuk meningkatkan kesadaran dan partisipasi publik. Temuan penelitian menunjukkan bahwa strategi berbasis konten interaktif, kolaborasi dengan tokoh publik (influencer), serta optimalisasi algoritma media sosial secara signifikan dapat meningkatkan efektivitas penyebaran nilai-nilai Pancasila. Studi ini menyimpulkan pentingnya adaptasi strategi komunikasi terhadap perkembangan teknologi digital dan karakteristik audiens kontemporer. Hal ini krusial untuk memastikan nilai-nilai nasional tetap relevan, resilien, dan diterima dengan baik oleh generasi muda di tengah arus globalisasi yang dinamis. Kata-kata Kunci: Nilai pancasila; media sosial; communication pattern.